Agglomeration and firm wage inequality: Evidence from China. (21st December 2020) - Chen, Anping; Dai, Tianshi; Partridge, Mark D.
Abstract: There is a large literature examining the effects of agglomeration on income distribution but less is known about its effects in developing countries. In this study, we apply panel data from a microfirm‐level survey and from city‐level data to investigate whether there is a causal relationship between agglomeration and establishment wage dispersion in China. Given the potential endogeneity of city size, we employ an instrumental variable regression approach. We find strong evidence that agglomeration has significant effects on wage inequality in the short and long run. The link between agglomeration and wage inequality is heterogeneous across regions. The spatially varying results appear to be due to different stages of development. Our results are consistent with the sorting models in that it appears that the most productive and least productive firms are relatively thriving in coastal cities, but not inland.